2021
DOI: 10.1093/jpids/piab050
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal Edema and Neck Pain in Multisystem Inflammatory Syndrome in Children (MIS-c)

Abstract: We defined the prevalence of neck pain, trismus, or dysphagia (28.4%) and retropharyngeal edema (2.9%) among 137 patients with multisystem inflammatory syndrome in children (MIS-c). Retropharyngeal edema or phlegmon has been documented radiologically in at least 9 children. Symptoms of neck inflammation are common in MIS-c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
19
2
Order By: Relevance
“…Interestingly, it seems that many clinicians around the world have questioned the link between MIS-C and retropharyngeal phlegmon. One study suggests that 28% of patients diagnosed with MIS-C at their institution had neck complaints due to retropharyngeal edema [ 19 ]. Even though most of these patients received antimicrobials in addition to anti-inflammatory treatment, retrospective reviews suggested that the retropharyngeal edema was inflammatory rather than infectious [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it seems that many clinicians around the world have questioned the link between MIS-C and retropharyngeal phlegmon. One study suggests that 28% of patients diagnosed with MIS-C at their institution had neck complaints due to retropharyngeal edema [ 19 ]. Even though most of these patients received antimicrobials in addition to anti-inflammatory treatment, retrospective reviews suggested that the retropharyngeal edema was inflammatory rather than infectious [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that 28% of patients diagnosed with MIS-C at their institution had neck complaints due to retropharyngeal edema [ 19 ]. Even though most of these patients received antimicrobials in addition to anti-inflammatory treatment, retrospective reviews suggested that the retropharyngeal edema was inflammatory rather than infectious [ 19 ]. It is worth noting that otolaryngologic manifestations such as retropharyngeal edema may often be overlooked during the exclusionary process of MIS-C diagnosis and not be considered one of the organ systems with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Her CT scan nding of retropharyngeal uid collection led to treatment for septic shock in the setting of a retropharyngeal abscess as the alternative diagnosis, and she was treated accordingly. Cases of MIS-C with retropharyngeal edema and/or phlegmon have been reported, though they are neither common nor de ning features of MIS-C (3,4). Antibodies against SARS-CoV-2 viral spike proteins are elicited by vaccines and confer immunity, whereas COVID-19 antibody tests that detect nucleocapsid proteins of the SARS-CoV-2 virus indicate natural infection (15).…”
mentioning
confidence: 99%
“…Neck pain has been reported in more than one-quarter of children with MIS-C, along with other otolaryngologic symptoms such as neck swelling, dysphagia, trismus, stridor and drooling [ 115 117 ]. Cervical imaging with US or contrast-enhanced CT might be requested to assess for signs of inflammation.…”
Section: Imaging Findings In Multisystem Inflammatory Syndrome In Chi...mentioning
confidence: 99%
“…Cervical imaging with US or contrast-enhanced CT might be requested to assess for signs of inflammation. The most common abnormalities are retropharyngeal edema and cervical lymphadenopathy [ 14 , 22 , 80 , 81 , 115 , 118 ] (Fig. 15 ).…”
Section: Imaging Findings In Multisystem Inflammatory Syndrome In Chi...mentioning
confidence: 99%